PENGARUH PENAMBAHAN GAMBUT DAN SEKAM PADI PADA MEDIA TANAM ALLUVIAL TERHADAP PERTUMBUHAN BIBIT MAHONI (Swietenia mahagoni) DI PERSEMAIAN - Sepriani, Dwi; Latifah, Siti; Ardian, Hafiz (Universitas Tanjungpura, 2014)
Mahogany is a pioneer plant that can grow well in brackish sand near beach. Mahogany trees are also widely used as a bioremediation agent. Mahogany plants that will be used as a bioremediation agent must be a good seed , one of the factors that must be corrected to obtain good seed is by providing a good planting media as well. In West Kalimantan, there are a lot of alluvial soil that can be used as a medium of nursery . Alluvial soil is generally acidic (low pH) and nutrient poor so it will be a problem when it is used as a medium of nursery. The attempts to overcome this problem is by adding peat and rice husk on alluvial palanting media . This study was aimed to determine the effect of peat and rice husk on alluvial planting media on the growth of mahogany seedlings in the seedbed. According to analysis carried out showed there were not significantly different between treatments, but when viewed from the mean of plant height and the number of leaf growth, treatment B with the comparison of alluvial soil , peat and rice hulls (5:5:0) was the highest growth of trunks and leaves . Based on the observation, the largest growth of trunk diameter was on treatment C that was 0:59 mm. The difference of diameter growth at every treatment is essentially influenced by many factors, both external factors from natural ( climate and environment ) and internal factors (genetic) of seed plants. Key words: Planting media, peat, rice husk, alluvial, growth of mahogany seedling.